The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.3802/jgo.2008.19.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of pretreatment laparoscopic surgical staging in patients with locally advanced cervical cancer: results of a prospective study

Abstract: Objective: To prospectively evaluate the feasibility, safety, and survival of laparoscopic surgical staging in patients with locally advanced cervical cancer. Methods: From Oct 2001 to Jul 2006, a total of 83 consecutive patients were eligible for inclusion and underwent laparoscopic surgical staging. Results: Three patients with intraoperative great vessel injury and 1 patient in whom the colpotomizer was unable to be inserted were excluded. Laparoscopic surgical staging was feasible in 95.2% (79/83). Immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Nodal status was determined by magnetic resonance imaging of the pelvis 6 positron emission tomography except for 36 patients who also underwent laparoscopic lymph node staging as a part of our previous clinical trial. 14,15 HPV status was evaluated from the cervical smear collected prior to radiotherapy using the Hybrid Capture II system (HC2; Digene Corporation, Gaithersburg, MD). HC2 test uses an RNA probe mixture of 13 high-risk HPV types and detects HPV types of 16,18,31,33,35,39,45, 51, 52, 56, 58, 59 and 68.…”
Section: Study Population Hpv Dna Test and Radiotherapymentioning
confidence: 99%
“…Nodal status was determined by magnetic resonance imaging of the pelvis 6 positron emission tomography except for 36 patients who also underwent laparoscopic lymph node staging as a part of our previous clinical trial. 14,15 HPV status was evaluated from the cervical smear collected prior to radiotherapy using the Hybrid Capture II system (HC2; Digene Corporation, Gaithersburg, MD). HC2 test uses an RNA probe mixture of 13 high-risk HPV types and detects HPV types of 16,18,31,33,35,39,45, 51, 52, 56, 58, 59 and 68.…”
Section: Study Population Hpv Dna Test and Radiotherapymentioning
confidence: 99%
“…First, pathologic confirmation of LN metastasis is available, enabling a more tailored radiotherapy. 8 Because imaging studies, such as CT, MRI, or PET, are inaccurate for predicting LN metastases, primary radiotherapy may result in undertreatment (resulting from a false negative) and overtreatment (resulting from a false positive). 20 As such, radiotherapeutic overtreatment is associated with complications including bowel perforation, and an accurate diagnosis via surgical staging and tailored radiotherapy is essential.…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, a prospective study conducted between 2001 and 2006 demonstrated the feasibility and safety of this strategy. 8 Because radiotherapy and pelvic LND are known risk factors for lymphedema, patients treated with both modalities are expected to experience this complication more frequently. 9 Nevertheless, no previous study has compared the incidence of lymphedema or LEE in cervical cancer patients considering the use of primary versus pretreatment laparoscopic staging followed by radiotherapy.…”
mentioning
confidence: 99%
“…1 Lymph nodes (LNs) metastasis is an important prognostic factor in not only that it is the most significant prognostic factor in early-stage cervical cancer but also that the field of RT depend on the extent of LN involvement. 2 However, the current clinical International Federation of Gynecology and Obstetrics (FIGO) staging system does not consider LN status, 3 which results in some discrepancies between FIGO stage and prognosis. In addition, preoperative imaging studies were not known to be satisfactorily sensitive for detecting LN metastasis in cervical cancer.…”
Section: Introductionmentioning
confidence: 99%